GAMBARAN KARAKTERISTIK PASIEN SKIZOFRENIA DI RSUD DR. GUNAWAN MANGUNKUSUMO KABUPATEN SEMARANG - Muthia Aulia Permatasari; Rihadini Rihadini; Romadhoni Romadhoni (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Mental health problems are one of the health problems in various countries around the world, including Indonesia. Schizophrenia is the most common psychotic disorder and due to the increasing number of schizophrenia patients in Indonesia, especially in Central Java Province, this study aims to describe the distribution of schizophrenia patient characteristics at Dr. Gunawan Mangunkusumo Regional Public Hospital Semarang Regency. This research is a non-experimental quantitative research using descriptive study with purposive sampling. Data were collected by interviewing the patient's family or guardian and using medical records of patients diagnosed with schizophrenia at Dr. Gunawan Mangunkusumo Regional Public Hospital Semarang Regency. The results of research showed the proportion of patients schizophrenia was highest at the age of 26-45 years old  in 48 people (50.5%), 66 people from male category (69.5%), 33 people with high school education (34.7%), 57 people unmarried (60%), 60 people unemployed (63.2%), 49 people with unspecified schizophrenia (51.6%), relapse that often occurs (43.2%) >2 times in 41 people, 72 people with no family history disease (75.8%). The characteristics of schizophrenia patients at Dr. Gunawan Mangunkusumo Regional Public Hospital were mostly in the age group of 26-45 years, male, high school education, unmarried, unemployed, unspecified schizophrenia type, relapse >2 times, and no family history